Mechanical and Ultrastructural Properties of Eggshell in Two Egyptian Native Breeds of Chicken - Radwan, Lamiaa M.; Fathi, M.M.; Galal, A.; El-Dein, A. Zein (International Journal of Poultry Science, 2009)
The objective of the study was to assess mechanical and ultrastructural properties of eggshell in Dandarawi and Fayoumi chicken breeds. At 30 weeks of age, 180 eggs (90 of each breed) were randomly chosen. The results showed that the Fayoumi eggs had significantly higher specific gravity and mechanical properties values (thickness and breaking strength of eggshell) than that of Dandarawi ones. With respect to ultrastructural traits, it could be noticed that the relative palisade layer (effective thickness) of Fayoumi eggs was significantly higher than that of Dandarawi ones. Opposite trend was noticed for relative cap layer. Concerning ultrastructural variants, the Fayoumi eggs owned shells with significantly higher values of confluence and cuffing traits. Conversely, the Dandarawi eggs have superior values of fusion, alignment and type B's traits than Fayoumi ones.